Microbial profile of chicken-based ready-to-cook frozen foods sold in Mymensingh city, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2025)
Demand for quick meals, such as ready-to-cook (RTC) foods, has been rising among modern consumers due to changing lifestyles worldwide, including in Bangladesh. However, these foods have been linked to several foodborne diseases, posing a significant threat to public health. As a result, assessing the microbial quality of RTC food products has become essential. This study aimed to evaluate the microbial quality of commonly available chicken-based RTC frozen foods in the markets of Mymensingh city. A total of 50 samples from five distinct types, collected from various retail points, were analyzed for total counts of aerobic bacteria, Staphylococcus spp., and Enterococcus spp., to determine how these loads compare against established safety standards. Correlations between different microbial loads were also examined. Generally, high levels of contamination were observed in almost all samples, except for low enterococcus counts in spring rolls. The mean counts of aerobic plate count (APC), total staphylococci count (TSC), and total enterococci count (TEC) across different food types ranged from 4.56 to 7.14 log CFU/g, 1.30 to 6.14 log CFU/g, and 1.24 to 3.56 log CFU/g, respectively. Two items, samosa and sausage, were identified as the most unsatisfactory in terms of microbial quality. Food manufacturers and regulatory authorities should focus on reducing contamination risks and regularly monitoring the food production chain. Consumers should also carefully follow cooking instructions and, if possible, avoid high-risk products. These findings underscore the need for strengthened hygiene practices, stricter regulatory monitoring, and improved quality control measures to ensure safer production and distribution of RTC chicken products in Bangladesh.Asian Australas. J. Food Saf. Secur. 2025, 9(2), 47-56